2012
DOI: 10.1038/oncsis.2012.26
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic control of metastasis-associated protein 1 gene expression by hepatitis B virus X protein during hepatocarcinogenesis

Abstract: Expression of metastasis-associated protein 1 (MTA1) gene correlates with the degree of invasion and metastasis in hepatocellular carcinoma (HCC). Expression of MTA1 is induced by hepatitis B virus X protein (HBx); however, little is known about the transcriptional regulation of MTA1 gene expression. Here, we report that the 5′-flanking region of the human MTA1 promoter contains two CpG islands. Transient expression of HBx in Chang liver cells increased the methylation of the CpG island1 from 18 to 49% when me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…This effect can be reversed by 5‑aza‑CdR, a methyl enzyme inhibitor [ 27 ]. Similar results are observed in protocadherin 10 (PCDH10), caveolin-1, and metastasis-associated protein 1 (MTA1) [ 28 , 29 , 30 ]. Some normally-hypermethylated intragenic CpG islands (mCGIs) have been observed to be hypomethylation before the development of HCC in HBx transgenic mouse liver.…”
Section: Epigeneticssupporting
confidence: 73%
“…This effect can be reversed by 5‑aza‑CdR, a methyl enzyme inhibitor [ 27 ]. Similar results are observed in protocadherin 10 (PCDH10), caveolin-1, and metastasis-associated protein 1 (MTA1) [ 28 , 29 , 30 ]. Some normally-hypermethylated intragenic CpG islands (mCGIs) have been observed to be hypomethylation before the development of HCC in HBx transgenic mouse liver.…”
Section: Epigeneticssupporting
confidence: 73%
“…In HCC of HBV etiology, the normally silenced metastasis-associated protein 1 ( MTA1 ) gene was upregulated by recruitment of DNMT3a and DNMT3b leading to hypomethylation of its promoter and increasing the tumor metastatic disposition [ 23 ]. Additionally, DNMT3b was elsewhere reported to be overexpressed by telomerase reverse transcriptase ( TERT ) in HCC.…”
Section: Dna Modificationsmentioning
confidence: 99%
“…Recent studies have reported that HBx plays an critical role in promoting the invasive and metastatic properties of intrahepatic and extrahepatic metastases of HCC, and poor prognosis in hepatitis B virus-related HCC 5 - 7 . HBx increases the invasion potential by upregulating the expression of metastasis-associated proteins 8 , vascular endothelial growth factors, the membrane-type matrix metalloproteinases 9 and miR-148a 6 , which contributes to HCC cells invasion and metastasis. These evidence implicated that HBx play a role not only in inducing development of HCC, but also in promoting malignant behaviors of HCC cells.…”
Section: Introductionmentioning
confidence: 99%